Severe Hyperacusis, Photophobia, and Skin Hypersensitivity - Alessandra Barbara Fioretti; Theodoros Varakliotis; Otello Poli; Manuela Cantagallo; Alberto Eibenstein (Case Reports in Otolaryngology)
We report a case of a patient with severe hyperacusis, photophobia, and skin hypersensitivity. The patient was initially treated with sound therapy and medical therapy for 4 months and successfully with a selective serotonin reuptake inhibitor (SSRI) and cognitive behavioral therapy which improved her mood and the tolerance for sounds and light.